Dimensional stability of metal optics on nickel plated AlSi40 - Kinast, Jan; Grabowski, Kevin; Gebhardt, Andreas; Rohloff, Ralf-Rainer; Risse, Stefan; Tuennermann, Andreas (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
Ultra precise mirrors are particularly useful for space applications and scientific instrumentations for large telescopes, covering a highly variable temperature range.
CRIS-Team Scopus Importer:2023-04-20